Strength properties of reinforced peat using fiber- polyesterand shredded rubber-crumb as reinforcement material - Norazzlina, M.Sa'don; Abdul Razak, Abdul Karim; Siti Noor Linda, Taib; Mahshuri, Yusof (2017)
This paper presents an investigation of the strength improvement of reinforced peat by using the fiber reinforcement techniques of the lightweight waste material, i.e., tire-waste disposal. The fiber-polyester and shredded rubber crumb are extracted and process for the collected tire-waste disposal. In this study, the fiber-polyester and shredded rubber-crumb are mixed with peat (Pt), with undrained shear strength, cu of <10 kPa and 5 % cement content, which act as a binder. The peat samples are mixed at various percentages of fiber-polyester and shredded rubber-crumb. The compacted fiber-reinforced peat samples were prepared at optimum moisture content, mixes thoroughly to a uniform condition by laboratory mixer and air cured for 7 and 28 days in a single batch. The strength improvement of undrained shear strength, cu of >100 kPa is targeted at minimal percentages of cement added. The Unconfined Compression Strength (UCS) and California Bearing Ratio (CBR) tests are performed for determination of the engineering properties of fiber-reinforced peat. Based on the results obtained, one can be seen that both fiber-polyester and shredded rubber crumb shows an increment in unconfined compressive strength value of 214 kPa and 55 kPa, respectively. In summary, the study shown that, the inclusion of fiber-polyester and shredded rubber-crumb from tire-waste disposal increased the effective contact area between reinforced material and peat, which then improved the strength significantly, and the used of tire-waste disposal for the construction may not only provide the alternative mean of recycling and reusing, however, it also addressed economic and environmental concerns and reduce construction cost by making the best use of locally available materials